LiNi0.5Mn1.5O4 cathode microstructure for all-solid-state batteries - Lee, HJ; Liu, X; Chart, Y; Tang, P; Bae, J-G; Narayanan, S; Lee, JH; Potter, RJ; Sun, Y; Pasta, M (American Chemical Society, 2022)
Solid-state batteries (SSBs) have received attention as a next-generation energy storage technology due to their potential to superior deliver energy density and safety compared to commercial Li-ion batteries. One of the main challenges limiting their practical implementation is the rapid capacity decay caused by the loss of contact between the cathode active material and the solid electrolyte upon cycling. Here, we use the promising high-voltage, low-cost LiNi0.5Mn1.5O4 (LNMO) as a model system to demonstrate the importance of the cathode microstructure in SSBs. We design Al2O3-coated LNMO particles with a hollow microstructure aimed at suppressing electrolyte decomposition, minimizing volume change during cycling, and shortening the Li diffusion pathway to achieve maximum cathode utilization. When cycled with a Li6PS5Cl solid electrolyte, we demonstrate a capacity retention above 70% after 100 cycles, with an active material loading of 27 mg cm–2 (2.2 mAh cm–2) at a current density of 0.8 mA cm–2.